2006
DOI: 10.1086/507821
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Catheter-Related Infections in a Hemodialysis Unit

Abstract: A hierarchy of infection risk associated with vascular access type is evident. Native arteriovenous fistulae should be recommended for all patients receiving chronic hemodialysis, to minimize infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
3
9
1
2
Order By: Relevance
“…The majority of the present BSIs were caused by gram positive micro- organisms, while the two most common pathogens isolated were, not surprisingly, the skin-derived Staphylococcus aureus and Staphylococcus epidermis , a finding consistent with other investigators' experience 8,9,14,15,22.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The majority of the present BSIs were caused by gram positive micro- organisms, while the two most common pathogens isolated were, not surprisingly, the skin-derived Staphylococcus aureus and Staphylococcus epidermis , a finding consistent with other investigators' experience 8,9,14,15,22.…”
Section: Discussionsupporting
confidence: 91%
“…One fourth of the bacteremic episodes were caused by gram-negative pathogens resistant to common antimicrobial agents, a proportion consistent with prior studies 9,10,15,22. It is worth noting that a substantial percentage of the gram-negative isolates (25%) were sensitive only to colistin.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A study 16 that aimed to identify the incidence of infection and evaluate the profi le of microorganisms isolated showed that 35% of bacteremic episodes were caused by gramnegative bacteria, a rate consistent with those reported in other studies [17][18][19] . Other study that use the medical records of 239 patients undergoing hemodialysis at the Department of Nephrology of the University Hospital of Heraklion, Crete, Greece, identify that, 3 out of 8 isolated (37.5%) Enterobacter spp.…”
Section: Discussionsupporting
confidence: 78%
“…Several multicenter studies demonstrate a hierarchy of infection risk associated with vascular access type (Table 1) [13,14,[20][21][22][23].…”
Section: Type Of Accessmentioning
confidence: 99%